Experimental study of dry stone masonry walls using digital reflection photoelasticity. (8th September 2020) - Kumar, Pankaj; Hariprasad, M.P.; Menon, Arun; Ramesh, K.
Abstract: Response of dry stack stone masonry walls under mechanical loading is complex and difficult to determine, mainly due to heterogeneous and discrete nature of the components of the stone wall. In this paper, reflection photoelasticity is used on scaled down models of stone masonry wall under uniaxial compression. Two walls are tested, and the methods to obtain near perfect dry stack masonry for reflection photoelastic studies are presented. Five‐step phase‐shifting methods are employed with TFP/RGB photoelasticity to quantitatively analyse the mechanical behaviour of the dry stack masonry walls. Isochromatics and isoclinic data are processed to obtain other whole field experimental stress data. Highly stressed zones are observed resulting in distinctive localised vertical failure in some of the stone units. In dry stack masonry construction, the failure mechanism is found to be dictated by the contact mechanics, which are governed by the non‐uniformity of block geometry even in very regular dry stack masonry.